Is disclosure of corporate social responsibility associated with firm performance? - Paiva, I.; Gavancha, I. (II Internacional Forum on Management, 2018)
The relevance of ethics to the management of modern companies has gradually increased. In recent years, economic, environmental and social information has become a key issue in the strategic agenda of competitive companies. This study investigates the relationship between the disclosure of corporate social responsibility (CSR) reporting and firms' performance. We use a sample of 51 firms belonging to the World Business Council for Sustainable Development in Portugal. We construct an index of CSR based on the content analysis of the companies' sustainability reports. Contrary to previous literature, we did not find a relationship between corporate social responsibility disclosure in Portuguese firms and their financial performance. However, additional results demonstrated that social responsibility disclosure in larger firms is associated with a higher level of performance.